Posthospital Discharge Medical Care Costs and Family Burden Associated with Osteoporotic Fracture Patients in China from 2011 to 2013 - Zhao Xie; Russel Burge; Yicheng Yang; Fen Du; Tie Lu; Qiang Huang; Wenyu Ye; Weihua Xu (Journal of Osteoporosis)
Objectives. This study collected and evaluated data on the costs of outpatient medical care and family burden associated with osteoporosis-related fracture rehabilitation following hospital discharge in China. Materials and Methods. Data were collected using a patient questionnaire from osteoporosis-related fracture patients (N = 123) who aged 50 years and older who were discharged between January 2011 and January 2013 from 3 large hospitals in China. The survey captured posthospital discharge direct medical costs, indirect medical costs, lost work time for caregivers, and patient ambulatory status. Results. Hip fracture was the most frequent fracture site (62.6%), followed by vertebral fracture (34.2%). The mean direct medical care costs per patient totaled 3,910¥, while mean indirect medical costs totaled 743¥. Lost work time for unpaid family caregivers was 16.4 days, resulting in an average lost income of 3,233¥. The average posthospital direct medical cost, indirect medical cost, and caregiver lost income associated with a fracture patient totaled 7,886¥. Patients’ ambulatory status was negatively impacted following fracture. Conclusions. Significant time and cost of care are placed on patients and caregivers during rehabilitation after discharge for osteoporotic fracture. It is important to evaluate the role and responsibility for creating the growing and inequitable burden placed on patients and caregivers following osteoporotic fracture.